Pandemic solidarity : mutual aid during the Covid-19 crisis - Sitrin, Marina; Sembrar, Colectiva; Solnit, Rebecca (FireWorks (Pluto Press), 2020)
In times of crisis, when institutions of power are laid bare, people turn to one another. Pandemic Solidarity collects firsthand experiences from around the world of people creating their own narratives of solidarity and mutual aid in the time of the global crisis of Covid-19. The world's media was quick to weave a narrative of selfish individualism, full of empty supermarket shelves and con-men. However, if you scratch the surface, you find a different story of community and self-sacrifice. Looking at eighteen countries and regions, including India, Rojava, Taiwan, South Africa, Iraq and North America, the personal accounts in the book weave together to create a larger picture, revealing a universality of experience - a housewife in Istanbul supports her neighbour in the same way as a teacher in Argentina, a punk in Portland, and a disability activist in South Korea does. Moving beyond the present, these stories reveal what an alternative society could look like, and reflect the skills and relationships we already have to create that society, challenging institutions of power that have already shown their fragility.